School bullying behaviors and victimization in Thai children and adolescents with comorbid attention deficit hyperactivity disorder, anxiety disorders, and oppositional defiant disorder - Prasartpornsirichoke, Jirada; Pityaratstian, Nuttorn; Pongparadorn, Warunya (Chulalongkorn Medical Journal, 2022)
Background: Bullying in school is a chronic social problem which has life-time impact. The prevalence of school bullying in Thai children and adolescents with attention deficit hyperactivity disorder (ADHD) is significantly higher than other groups. However, there is no research work has been done on the association and impact of the comorbidity of ADHD, anxiety disorder, and oppositional defiant disorder (ODD) on bullying in school. Objectives: This study aimed to examine the prevalence of school bullying in Thai children and adolescents with comorbid ADHD, anxiety disorders, and ODD at King Chulalongkorn Memorial Hospital and to investigate associations and effects of the comorbidity of anxiety disorders and ODD on bullying in school. Methods: Cross-sectional descriptive study is based on data collected from children and adolescents with ADHD who received the treatment at King Chulalongkorn Memorial Hospital from September 2018 to May 2019. The data were collected by questionnaires including questionnaire of demographic data, the Thai version of the revised Olweus bully/victim questionnaire (BVQ), the Thai version of Screen for Child Anxiety Related Disorders (SCARED), and the Thai version of the Swanson, Nolan, and Pelham Rating Scale (SNAP-IV) in short form. Results: The prevalence of school bullying victimization in Thai children and adolescents with ADHD was 69.4%. Most children and adolescents with ADHD were in a role of victim (60.5%). The associated factors of victimization in school were patient’s education level, type of private school, and the comorbidity of anxiety disorder. The associated factors of bullying behavior were male patients and the comorbidity of ODD with shown moderate to severe symptom. Conclusion: The prevalence of school bullying victimization in Thai children and adolescents with ADHD is 69.4%. The comorbidities of anxiety disorder and ODD are associated with victimization and bully behaviors in school respectively.